ANALISIS RELEVANSI KURIKULUM INTERNATIONAL CLASS PROGRAM (ICP) FAKULTAS MIPA UNIVERSITAS NEGERI MAKASSAR DENGAN KURIKULUM SMP RSBI DI KOTA MAKASSAR - Ria Rezki Hamzah (Teknosains, 2014)
The curriculum is one component that has a strategic role in the education system. Curriculum on International Class Program UNM Faculty of Science, has studied the course material to the students as prospective educators to consider the needs of field-oriented learners, particularly RSBI. The purpose of this study was to: (i) conduct an assessment of ICP Curriculum, State University of Makassar with the Education Unit Level Curriculum RSBI junior in Makassar to know kerelevanannya, (ii) quantify the proportion of material Curriculum Education Unit RSBI junior teaching science in City Makassar contained in the curriculum ICP Faculty of Science, State University of Makassar. This research is ex post facto research with data collection techniques through the study documentation and interviews. Data analysis using matrix method and presented descriptively.The results showed that: (i) curriculum with the curriculum of the UNM Faculty ICP RSBI junior in Makassar is relevant, judging from the number of points of the subject / sub teaching science subject that is in the course materials based on ICP analysis performed relevance, (ii) that contains several courses subject / sub subject science teaching also has a fairly high points, reaching 33.3% in Basic Biology courses, and 31.4% in the high School Physics courses Practicum. Based on the interviews conducted, by the author of the given input to produce university educators with international class to send its students to perform practical field experience in junior RSBI..